Bats as hosts of zoonotic pathogens - Thalin, Therese (2021)
Bats belong to the order Chiroptera, one of the most species rich mammalian groups of Sweden, but it is also the most threatened one. Nineteen different bat species have been found in Sweden, of which 12 are red-listed. Globally rodents and bats are the animal groups known to host most zoonotic pathogens. Bats are known to carry rabies, even though there has been no discovery of cases in Sweden where humans have been infected. Bats in Sweden have previously been found to carry rabies specific antibodies, thus indicating that rabies is circulating among the Swedish bat populations. Various hantaviruses have been found in insectivorous bats, however in Sweden so far only rodents are identified hosts. In Sweden, the knowledge of pathogens hosted by bats is generally low. Thus, the aim of this study was to explore and answer the following three questions: (I) To which extent are Swedish bats, focusing on the Daubenton’s bat, reservoirs of zoonotic pathogens? (II) Do bats in Sweden host puumala orthohantavirus (PUUV)? (III) If bats host zoonotic pathogens, is there a conflict between nature conservation and public health?